Column adsorption study for the removal of chromium and manganese ions from electroplating wastewater using cashew nutshell adsorbent. Issue 1 (1st January 2020) - Yahya, M. D.; Aliyu, A. S.; Obayomi, K. S.; Olugbenga, A. G.; Abdullahi, U. B.
Abstract: The aim of this study is to evaluate the potential of cashew nutshell activated with H2 SO4 as adsorbent for the removal of Cr and Mn (II) ions from wastewater. In this study, cashew nutshell (CNS) adsorbent was prepared using shells of cashew nut ( Anacardium occidentale ) by chemical activation. Cashew nutshells were crushed for size reduction and the resulting crushed shells were immersed in 1.0 mol L −1 H2 SO4 at a rate of 1:10 (m/v) with a constant stirring at 60°C for 4 h. Proximate analysis was carried out according to standard analytical methods and determination of pH, bulk density, and iodine number was conducted. The morphology and functional groups present were investigated by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FT-IR) spectroscopy. The surface area, pore volume, and pore size distribution were also characterized by N2 adsorption at 77 K using BET. Continuous adsorption study in a fixed-bed column was carried out by using CNS as an adsorbent for the removal of chromium and manganese ions from electroplating wastewater. The effect of flow rate, influent concentration, and bed depth were investigated on the adsorption characteristics of the CNS adsorbent. Three dynamic model Clark, Yoon-Nelson, and Adams-Bohart were applied using the experimental data to predict the breakthrough curves using linear regression to determine the characteristic parameters of the column that are useful for process design. Significant values in the moisture, ash content, volatile matter, iodine number, and zero-point of charge were obtained on the adsorbent and compared to literature. SEM images revealed irregular pore structure before adsorption and pores of the CNS adsorbent were filled with chromium and manganese ions after adsorption. The FT-IR adsorption bands observed in the CNS sample confirmed the presence of hydroxyl (-OH), carbonyl, and carboxylic (-COOH) groups involved in sorption of chromium and manganese ions onto surface of CNS adsorbent. The result showed highest BET specific surface area of the adsorbent sample obtained as 608.2 m 2 /g, pore volume and diameter of 0.2209 cm 3 /g and 2.116 nm, respectively. The column parameters calculated showed the effectiveness of the column at a flow rate of 5.0 ml/min, bed height of 10 cm and concentration of 20.3 mg/l Mn ion and 21.05 mg/l Cr ion. The percentage removal of Cr ions was 56.40% at an adsorption capacity of 10.79 mg/g and the percentage removal of Mn (II) ions was 53.09%, at an adsorption capacity of 9.82 mg/g. The Yoon-Nelson and Clark models were found suitable for the description of the breakthrough curve. Results reveal that quality cashew nutshell (CNS) adsorbent can be produced from Cashew nutshell thereby serving as an alternative to commercial adsorbent for heavy metal removal from wastewater.